Practical aspects of DSS design for commodities transportation during special events. - Zacharias, Manousaridis (Software engineering notes.)
Transport firms that daily pickup or deliver commodities encounter a plethora of problems relating to their Vehicle Routing and Scheduling (VRS) activities. To make decisions about Routing and Scheduling during special events is even more complicated process. During the Athens Olympic Games 2004 in Athens, the Vehicle Routing and Scheduling problem was very keen. Actually, the commodities transportation had to be done within strictly defined time-periods and under many security and traffic restrictions [2], [8]. "Xenios" is a specific DSS that was developed to assist the daily VRS activities of Greek transport firms during special events. This system incorporated essential functions of GIS, database systems and model management techniques to support overall routing, scheduling and decision-making processes for VRS problems encountered during the Athens 2004 Olympic Games (ATHENS 2004).Our work aimed at the successful setting up of DSS "Xenios" so that it could cover a wide range of variations of the VRS problem, especially problems with hard time-windows in the route generation [15], [17].The first step in the development of any specific DSS is the identification of the applying problem dimensions [3], [7], [10]. In order to make easier the development procedure, we tried to classify the most significant VRS problem dimensions that have common characteristics in groups. According to our consideration, this work could accelerate and ease the development of the specific DSS.